Efektivitas Penggunaan Metode Picture And Picture Dalam Pembelajaran Ips Sub Tema "Potensi Sumber Daya Air" Peserta Didik Kelas Vii Smp N 3 Sawit Tahun Ajaran 2015/2016 - SULIMAH, SITI (2016)
ABSTRACT The study was conducted in SMP Negeri 3 Palm Boyolali addressed at Jln. Solo-Yogja KM 14 Bendosari, Sawit subdistrict Boyolali. 57 374 zip code with the phone number (0271) 782579. The purpose of this study were (1) Determine the level of understanding of students in social studies learning material potential of water resources by using picture and picture, and (2) determine the effectiveness of the use of methods of picture and picture on the lessons IPS material potential of water resources. The study was conducted on all class VII as many as 231 students, divided into two classes, namely the experimental class and control class. No experimental class 4 class and control class there are three classes. Grades given experimental treatment using the picture and picture while the control group was given the material by using conventional methods such as cerama. The results of the study are (1) The use of methods of picture and picture can be used to improve student learning outcomes in social studies learning material potential of water resources, the result of the average value of student learning experimental class is higher than the control class. The average value of about pre-test and post test experimental class students at 15.69 while the control class is 9.71. (2) Results grade students experiment with control classes showed a difference, by Mann Whitney test value is the average class experiments using methods of picture and picture at 74.03 while the control class average value of 68.45, thus experiencing an increase in the average value of the experimental class at 15.69 while the control class is 9.71 suggesting that the method is more evektif picture and picture compared to conventional methods. Keywords: Improved Learning Outcomes, Effectiveness, Methods Picture And Picture.